Kajian Administratif, Farmasetis dan Klinis Resep Pasien Ispa di RSUD Bendan Kota Pekalongan - Eni Hafidzah; Musa Fitri Fatkhiya (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
ARI is an acute respiratory infection that affects one or more parts of the respiratory system. The high prevalence and risk factors in the prescription of ARI patients need to be considered in the completeness of the prescription and the provision of appropriate drugs to increase the effectiveness of treatment therapy. The purpose of this study was to determine the suitability of prescribing ARI patients aged 0-12 years administratively, pharmaceutically, and clinically based on PMK No. 72 of 2016. This type of research is descriptive observational and retrospective data collection. The sample used was the prescription of ARI patients at Bendan Hospital who met the inclusion criteria for the period April-May 2023, totaling 25 prescription sheets. The sampling technique used total sampling technique. The results showed that in administrative aspects including patient name, gender, age, address, doctor's name, SIP, telephone number, doctor's address, doctor's signature, prescription date was fulfilled 100% and body weight was fulfilled 92%. The pharmaceutical aspects include the name of the drug, dosage form, dosage strength, drug dosage, amount of drug, rules of use and how to use are fulfilled 100%. Clinical aspects include 100% indication accuracy, 100% dose accuracy and 52% drug interactions. It can be concluded that the suitability of prescribing ARI patients for children aged 0-12 years is administratively 100%, pharmaceutically 92%, and clinically 48%.